2012
DOI: 10.1002/pc.22180
|View full text |Cite
|
Sign up to set email alerts
|

Swelling, pH sensitivity, and mechanical properties of poly(acrylamide‐co‐sodium methacrylate) nanocomposite hydrogels impregnated with carboxyl‐functionalized carbon nanotubes

Abstract: A series of novel nanocomposite hydrogels were prepared by a cross‐linking copolymerization method. Structural and morphological characterizations of the nanocomposite hydrogels revealed that a good compatibility exists between poly(acrylamide‐co‐sodium methacrylate) [P(AM‐co‐SMA)] and carboxyl‐functionalized carbon nanotubes (MWNTs–COOH). The P(AM‐co‐SMA)/MWNTs–COOH nanocomposite hydrogels with a suitable MWNTs–COOH loading exhibited better swelling capability, higher pH sensitivity, good reversibility, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Therefore, increasing the content of the GO nanosheets results in the increase of the cross-linking density. At a moderate content, however, the GO nanosheets can be uniformly dispersed in the PAA matrix, and more PAA chains are enriched on the GO 20 surfaces through cross-linking, leading to a robust and flexible network structure translating into outstanding toughness and stretchability. The PAA concentration is also an important factor, since the variation in the water content is found to significantly influence 25 the elastic modulus, tensile strength and fracture energy of the GO/PAA nanocomposite hydrogels ( Fig.…”
Section: Characterizationmentioning
confidence: 98%
See 2 more Smart Citations
“…Therefore, increasing the content of the GO nanosheets results in the increase of the cross-linking density. At a moderate content, however, the GO nanosheets can be uniformly dispersed in the PAA matrix, and more PAA chains are enriched on the GO 20 surfaces through cross-linking, leading to a robust and flexible network structure translating into outstanding toughness and stretchability. The PAA concentration is also an important factor, since the variation in the water content is found to significantly influence 25 the elastic modulus, tensile strength and fracture energy of the GO/PAA nanocomposite hydrogels ( Fig.…”
Section: Characterizationmentioning
confidence: 98%
“…3e). Note that the healed sample, after having been cut off and treated at 45 o C for 20 48 h, can be stretched over 20 times (Fig. 3e and Video 3 †, ESI).…”
Section: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of the existing natural and synthetic hydrogels have poor mechanical properties, which unfortunately limit their applications in many fields where tough and flexible hydrogels are necessary. In this sense, a surge of research has been reported on the development of nanocomposite hydrogels reinforced with various nanofillers, including clay nanosheets [16], silica nanoparticles [6,9,17], graphene oxide (GO) nanosheets [7,[18][19][20][21][22] and carbon nanotubes [23]. Recently, we have prepared a high-strength GO/PAA nanocomposite hydrogels composed of a single network with dual crosslinking points through dynamic ionic interactions [7].…”
Section: Introductionmentioning
confidence: 98%
“…These days, number of materials has been used such as carbon nanotubes, graphene oxide, carbon dots, metal oxides and ceramics, etc. so as to make novel nanocomposite hydrogels having improved mechanical properties [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%